Wearable body sensor networks: State-of-the-art and research directions - Gravina, R.; Fortino, G. (IEEE Sensors Journal, 2021)
The term Body Sensor Network (BSN) was introduced less than twenty years ago. Since then, tremendous technical development and social changes attracted researchers from very diverse fields allowing to establish an incredibly rich interdisciplinary ecosystem. Although many former challenges have been tackled by consolidated literature, still today new research opportunities stem from recent advancements in IoT, machine learning, communication technologies, bio-materials and microelectronics. This work has a twofold objective: on the one hand aims to briefly review the state-of-the-art on more consolidated BSN literature and on the other hand surveys recent advancements enabled by Edge computing, microelectronics and communication novelty. An analysis of success stories of wearable devices, emerging real-world applications, and most recent research frontiers in the BSN domain complete the survey.